2022
DOI: 10.1186/s12909-022-03538-w
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a combined problem-based learning and flipped classroom teaching method in ophthalmic clinical skill training

Abstract: Background Previous studies have primarily implemented problem-based learning (PBL) or flipped classroom (FC) teaching models in different majors; however, research on the combined PBL-FC teaching method in clinical medicine is scarce. Therefore, we investigated the combined PBL-FC teaching method in teaching ocular trauma on students’ competencies. Method About 75 ophthalmology postgraduates were randomly divided into PBL-FC and traditional teachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
3
7
0
1
Order By: Relevance
“…Previous evaluations of a flipped classroom approach in ophthalmology teaching have involved medical students, specialist trainees, and other medical disciplines. 14,15,[22][23][24][25][26] Similar to some U.K. medical schools with a compulsory 5-to 10-day standalone ophthalmology rotation that includes core knowledge and skills (e.g., "sudden loss of vision," "acute red eye," direct ophthalmoscopy), 2 the Faculty of Medicine of the Chinese University of Hong Kong (CUHK) 5-day ophthalmology rotation includes examination skills training, clinical and surgical attachments, and case tutorials; the rotation forms part of a senior surgical dressership with other surgical subspecialties. Students need a concise, stimulating, and well-organized ophthalmology course with teaching materials that facilitate engagement and ideally synchronize with their existing knowledge to promote skills and knowledge retention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous evaluations of a flipped classroom approach in ophthalmology teaching have involved medical students, specialist trainees, and other medical disciplines. 14,15,[22][23][24][25][26] Similar to some U.K. medical schools with a compulsory 5-to 10-day standalone ophthalmology rotation that includes core knowledge and skills (e.g., "sudden loss of vision," "acute red eye," direct ophthalmoscopy), 2 the Faculty of Medicine of the Chinese University of Hong Kong (CUHK) 5-day ophthalmology rotation includes examination skills training, clinical and surgical attachments, and case tutorials; the rotation forms part of a senior surgical dressership with other surgical subspecialties. Students need a concise, stimulating, and well-organized ophthalmology course with teaching materials that facilitate engagement and ideally synchronize with their existing knowledge to promote skills and knowledge retention.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the difficulties, we identified and modified the shortcomings of existing pedagogies (i.e., flipped classroom, problem-based and casebased learning) to fit our needs. Flipped classroom had previously received generally positive feedback in ophthalmology teaching, 14,15,[22][23][24][25][26][27] but could also overburden students, especially if they are simultaneously involved in another clerkship 15 or the content emphasized memorization. 14 Therefore, we designed our module to provide standardized videos focusing on practical approaches to chief complaints and clinical examinations rather than purely content-based knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Men [ 19 ] showed that PBL combined with evidence-based learning (EBL) could improve the enthusiasm and initiative of thoracic surgery students and achieve satisfactory teaching effects. Wang [ 20 ] studied how to improve the learning effect of ophthalmology graduate students in the teaching of eye trauma, and finally believed that the method of PBL combined with Flipped Classroom(FC) would be more helpful to students without clinical experience. Hu [ 21 ] also affirmed the teaching effect of the combination of above two methods, but he believed that further optimization was needed for wider promotion.…”
Section: Discussionmentioning
confidence: 99%
“…Selain itu, mahasiswa juga dituntut untuk kritis, memiliki rasa ingin tahu yang tinggi, terbuka, dan kreatif dalam memecahkan masalah melalui kegiatan pencarian data dan diskusi kelompok. Hal ini didukung hasil penelitian sebelumnya yang menunjukkan bahwa implementasi FPBL dapat meningkatkan kemampuan berpikir kritis, kreativitas dalam memecahkan masalah, kemandirian, dan regulasi diri mahasiswa (Çakıroğlu & Öztürk, 2017;Damayanti et al, 2020;Hsia et al, 2021;Inayah et al, 2021;Mudhofir, 2021) Pada dimensi produk, penerapan FPBL dalam pembelajaran sains dapat meningkatkan penguasaan mahasiswa terhadap produkproduk sains yaitu teori, konsep, prinsip, serta hukum (Damayanti et al, 2020;Wang et al, 2022). Hal ini karena pelaksanaan pembelajaran dilaksanakan secara sistematis melalui metode ilmiah dengan melibatkan partisipasi mahasiswa secara aktif untuk menciptakan pembelajaran yang bermakna.…”
Section: Hasil Dan Pembahasanunclassified